2004
DOI: 10.1002/humu.20124
|View full text |Cite
|
Sign up to set email alerts
|

KCNJ11activating mutations in Italian patients with permanent neonatal diabetes

Abstract: Permanent neonatal diabetes mellitus (PNDM) is a rare condition characterized by severe hyperglycemia constantly requiring insulin treatment from its onset. Complete deficiency of glucokinase (GCK) can cause PNDM; however, the genetic etiology is unknown in most PNDM patients. Recently, heterozygous activating mutations of KCNJ11, encoding Kir6.2, the pore forming subunit of the ATP-dependent potassium (K(ATP)) channel of the pancreatic beta-cell, were found in patients with PNDM. Closure of the K(ATP) channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
94
1
4

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 24 publications
6
94
1
4
Order By: Relevance
“…2c). In agreement with this prediction, mutations at R50 impair ATP inhibition [30,[37][38][39] and can give rise to neonatal diabetes [12,30]. Mutation of either H46 or N48 might, therefore, be expected to influence the position of R50, and thereby destabilize ATP binding.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…2c). In agreement with this prediction, mutations at R50 impair ATP inhibition [30,[37][38][39] and can give rise to neonatal diabetes [12,30]. Mutation of either H46 or N48 might, therefore, be expected to influence the position of R50, and thereby destabilize ATP binding.…”
Section: Methodsmentioning
confidence: 61%
“…The commonest cause of permanent neonatal diabetes (PNDM) are heterozygous activating mutations in the KCNJ11, the gene encoding Kir6.2, which constitutes the pore-forming subunit of the K ATP channel in the pancreatic beta cell [7][8][9]. KCNJ11 mutations account for around 50% of cases of PNDM [7][8][9][10][11][12][13]. Some of these mutations lead to a more severe syndrome in which developmental delay and epilepsy accompany neonatal diabetes, a condition known as DEND syndrome [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mutation detection in six of these patients has been previously reported [9]. The newly identified patients, known here by patient numbers nd-CH/1 (R2011H), nd-MI/1 (V59M), nd-NA/9 (R201H) and nd-TN/1 (R201H), did not show any peculiar clinical feature.…”
mentioning
confidence: 57%
“…The discovery that activating mutations of KCJN11 causing permanent or transient neonatal diabetes can respond to sulfonylureas [1, 2, 4-8] opened the possibility of treating patients who have this genetic defect with oral hypoglycaemic agents. In previous studies [4,9], this report and in unpublished observations (F. Barbetti), the Italian Study Group of Early-Onset Diabetes has identified 16 unrelated subjects with eight different KCNJ11 mutations. To date, one subject with KCNJ11-related transient/relapsing neonatal diabetes [4] and ten patients from the Italian cohort of KCNJ11-related permanent neonatal diabetes mellitus have been successfully transferred from insulin to sulfonylurea.…”
mentioning
confidence: 74%
“…The intronless KCNJ11 gene was amplified in three overlapping fragments (B, C and D), with a primer pair previously described for B and C fragments [4] and modified for the D fragment (D forward: 5′ ccg ctg atc atc tac cat gtc 3′; D reverse: 5′ tac cac atg gtc cgt gtg tac 3′). We identified a heterozygous R201H mutation (c.602 G→A) that arose de novo in the patient.…”
mentioning
confidence: 99%